Automatic detection and identification of electric loads at the event of switching-on that load - Thiruvaran, T.; Phung, T.; Ambikairajah, E. (IEEE, 2013)
Automatic detection of the event of switching-on an electric load, estimation of that switch-on instant and subsequent automatic identification of that electric load using current transient signal around the switch-on instant are studied in this paper. The time variation of the current harmonics is used to first detect the event of switching-on an electric load and then spectral features extracted from the current harmonic signal around the estimated switching-on instant is used for automatic identification of that load. In particular, feature based on the second derivative of the magnitude of second harmonic of the current signal is proposed to be used for automatic detection of the event of switch-on. This feature provided an error rate of 9.4% of event detection with 0.27 seconds of average error in estimating the switch-on instant. Finally, the overall system that combines this detection of the event of switch-on and the automatic identification of that load gave an accuracy of 87.5% in a cross fold validation experiment tested with four loads.
Keywords: Electric load identification; transient current